Age & Sex Related Change in the Shape of the Human Pituitary Gland (Bangladesh Journal of Anatomy, 2013)
Context: The pituitary gland produces several hormones that regulate growth, metabolism and reproduction. Deviations from the normal functions of the gland certainly derange the harmony of life. Therefore, this study is important to determine the disease conditions of the gland and also for diagnosis and treatment of diseases of other endocrine organs. Many studies suggested that changes in the endocrine milieu may be reflected in pituitary morphology. The pituitary height in females was significantly greater than that in males. The decline in pituitary height with age may also reflect the process of aging and a physiological pituitary atrophy. Dynamic changes occur in the size, shape and signal intensity of the pituitary gland during life. These changes reflect the complex hormonal environment of the gland and are most pronounced at times of hormonal flux, such as menarche and pregnancy. The appearance of the pituitary gland in magnetic resonance imaging (MRI) of newborn infants differs from that of older children and adults. Previous observers have noted changes in the shape of the pituitary gland at different stages of life, which also reflect concurrent changing of hormonal level. Objective: To identify any variation of shape of the pituitary gland in relation to age & sex. Type of Study: A cross-sectional analytical type of study. Place & Period of Study: Department of Anatomy, Dhaka Medical College, Dhaka, from July 2009 to June 2010. Materials: About 60 (40 male and 20 female) postmortem human pituitary glands were collected from unclaimed dead bodies that were under examination in the morgue of the Department of Forensic Medicine, Dhaka Medical College Dhaka. The study was approved by the Ethical Review Committee (ERC) of Dhaka Medical College. Methods: The samples were divided into four groups. i.e. Group-A (20-29 years), Group-B (30-39 years), Group-C (40-49 years) and Group-D (50-59 years). The shape was recorded according to the grading system of Elster et al.(1990) , such as- a) Grade 1- Concave, b)Grade 2- Mildly concave, c)Grade 3 - Flat, d)Grade 4 - Mildly convex, e)Grade5-Moreconvex/rounded/spherical. Results: Grade 1 was found in 1(2.5%) male sample of group B and C & 1(5%) in female sample of group A. Grade 2 was noted in 3 (7.5%), 2 (5%), 3 (7.5%) and 1(2.5%) male samples of group A, B, C and D respectively. Grade 3 was found in 4 (10%), 5 (12.5%), 4 (10%) and 1(2.5%) male samples of group A, B, C and D respectively and about 1(5%), 2(10%) and 1 (5%) female samples of group A, B and C respectively. Grade 4 was noted in 2 (5%), 7(17.5%), 1(2.5%) and 1(2.5%) male samples of group A, B, C and D respectively and in 6(30%), 3(15%) and 1(5%) female samples of group A, B and C respectively. Grade 5 was noted in 2(5%) male samples of group B and D and in 1(5%), 3(15%) and 1(5%) female samples of group A, B and C respectively. Conclusion: The shape of the pituitary gland are tended to be changed in between sexes and with advancing ages. It was revealed in the study that, flat glands are more common in male while in female mildly convex gland was common. Rounded glands were found common in male in 50-59 years age group but could not be compared due to absence of female samples from that group. Further studies to find out the cause of this difference of shape between male & female glands with ages are recommended. DOI: http://dx.doi.org/10.3329/bja.v10i2.17287 Bangladesh Journal of Anatomy, July 2012, Vol. 10 No. 2 pp 68-72